2019
DOI: 10.1177/1476718x19849248
|View full text |Cite
|
Sign up to set email alerts
|

Let us play together! Can play tutoring stimulate children’s social pretend play level?

Abstract: Social pretend play may have a positive impact on children’s social development because it involves positive peer interactions and challenges their social-cognitive abilities. The current study aimed to investigate whether variations in play tutors’ active support and play management are associated with variations in children’s social pretend play level in the context of a pretend play tutoring intervention. Moreover, the moderating role of children’s social skills (cooperative behaviour and sociability) was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 19 publications
1
22
0
1
Order By: Relevance
“…The positive association with age corresponds with previous research findings and confirms the developmental pattern of social pretend play (Howes & Matheson, 1992). Furthermore, the results showed that more sociable children showed a higher quality social pretend play in general, which again is in line with the previous findings of Perren et al (2019). Children who enjoy social interaction may spend more time in social play and therefore may have more practice or experience, which could lead to higher play competence during social pretend play (Bodrova et al, 2013; Howes & Matheson, 1992).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The positive association with age corresponds with previous research findings and confirms the developmental pattern of social pretend play (Howes & Matheson, 1992). Furthermore, the results showed that more sociable children showed a higher quality social pretend play in general, which again is in line with the previous findings of Perren et al (2019). Children who enjoy social interaction may spend more time in social play and therefore may have more practice or experience, which could lead to higher play competence during social pretend play (Bodrova et al, 2013; Howes & Matheson, 1992).…”
Section: Discussionsupporting
confidence: 92%
“…Four playgroups were randomly selected to participate in a play tutoring intervention for six consecutive weeks. The intervention was similar to that described in Perren, Sticca, Weiss‐Hanselmann, and Burkhardt Bossi (2019). The play tutor brought a standardized set of role‐play materials, and both encouraged and guided the children in their play for 30 min per week.…”
Section: Methodsmentioning
confidence: 92%
“…To evaluate the promotional potential of providing roleplay material it is necessary to take adult behavior into account. Perren et al (2019) have shown that play tutoring -providing roleplay material and a high level of active play support -is an effective strategy for promoting children's social pretend play quality (within-person design). Accordingly, we hypothesized that children in the material condition would show higher levels of social pretend play quality than in the control condition, but lower levels than children in the play tutoring condition.…”
Section: The Current Study and Research Questionsmentioning
confidence: 99%
“…In the play phase the tutors used specific play supportive strategies (e.g., Prompting, Modeling), the promotional effect of which is supported by the results of Perren et al (2019). The tutoring followed a standardized schedule.…”
Section: Social Pretend Play Tutoringmentioning
confidence: 99%
See 1 more Smart Citation